2010
DOI: 10.1111/j.1553-2712.2009.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a New Model for Femoral Ultrasound‐guided Central Venous Access Procedural Training: A Pilot Study

Abstract: Objectives: Repetitive practice with feedback in residency training is essential in the development of procedural competency. Lightly embalmed cadaver laboratories provide excellent simulation models for a variety of procedures, but to the best of our knowledge, none describe a central venous access model that includes the key psychomotor feedback elements for the procedure, namely intravascular contents that allow for determination of correct needle position by either ultrasonographic imaging and ⁄ or aspirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 10 publications
0
30
0
Order By: Relevance
“…Several authors have documented success with teaching, demonstrating, and practicing highly skilled procedures such as femoral US-guided central venous access, tube thoracostomy, cricothyrotomy, and other technical surgical procedures using cadaver models (6)(7)(8)(9)(10)16,17). Frezza et al demonstrated that a cadaver training program can be an effective adjunct to training surgical residents in performance and interpretation of the FAST examination; in that study, free intraperitoneal fluid was simulated in cadaver models by infusing different volumes of normal saline, allowing residents to be tested on FAST examination performance and interpretation (10).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Several authors have documented success with teaching, demonstrating, and practicing highly skilled procedures such as femoral US-guided central venous access, tube thoracostomy, cricothyrotomy, and other technical surgical procedures using cadaver models (6)(7)(8)(9)(10)16,17). Frezza et al demonstrated that a cadaver training program can be an effective adjunct to training surgical residents in performance and interpretation of the FAST examination; in that study, free intraperitoneal fluid was simulated in cadaver models by infusing different volumes of normal saline, allowing residents to be tested on FAST examination performance and interpretation (10).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, cadaver models have been used to train residents in performance of the focused assessment with sonography in trauma (FAST) examination, by simulating free intraperitoneal fluid detected on US, and for demonstrating joint effusion (10)(11)(12). There are numerous applications of diagnostic and procedural bedside US that can be simulated with human cadaver models and thus used for medical education (6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Importancementioning
confidence: 99%
See 1 more Smart Citation
“…Second, cadavers used in this study were lightly embalmed. Though lightly embalmed cadavers preserve many of the natural tissue properties when compared with fully embalmed cadavers [14,20], it is not known how close the arterial characteristics are to the in vivo properties, which may affect torsional measurements. Though subjectively lightly embalmed arteries are similar to the arteries of PAD patients, this question requires more investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The marker deployment procedure was performed in n ¼ 28 legs of 14 lightly embalmed cadavers (eight male, six female, average 80 + 12 years old, range 49 -99 years) that died of causes unrelated to vascular disease. Use of lightly embalmed cadavers as opposed to those that are fully embalmed, allowed better preservation of natural tissue properties [14,20]. Arteries were pressurized (Harvard Apparatus Large Animal pump, Harvard Apparatus, Holliston, MA, USA) to 100 mmHg using a 37C radiopaque custom mixture fluid.…”
Section: Human Cadaver Modelmentioning
confidence: 99%